Disaster risk preparedness among people in isolated areas in the province of Zamboanga del Norte - Telen, Jay D.; Villadarez, Chile A. (2015)
This study aimed to assess the disaster risk preparedness among people in isolated areas in Zamboanga del Norte. It utilized the descriptive method of research through the use of questionnaire on disaster preparedness and documentary analysis. Results showed that a high percentage of the respondents are not prepared enough for the unpredictable outbreak of some disasters such as tsunami, volcanic eruption, tropical cyclone, storm surge, floods, thunderstorm and tornado. A significant difference existed on the preparedness of the respondents for the risks of the different disasters when grouped as to monthly income and length of residency which implied that those who have a good income have more advantage compared to those who have a very low income and that the respondents’ preparedness is limited to their length of residence in a particular place. The result further showed that no significant difference existed when respondents were grouped according to civil status and home which means that whether the respondents are single or married their preparedness is just the same and that the respondents’ preparedness are not influenced by whether owning or renting their houses. There is, therefore, a need for the provincial government to address this specific issue on disaster risk preparedness among isolated communities through creating education programs, conducting seminars, and establishing long-term monitoring procedures.
Keywords: Emergency management; Mindanao studies